Sepikul Segendongan: Budaya Hukum Kewarisan Adat Jawa Masyarakat Kaligesing, Kabupaten Purworejo, Jawa Tengah - Mastri Imammusadin (Dampeng: Journal of Art, Heritage and Culture, 2025)
Abstract: This article is a comprehensive study of the concept of sepikul segendongan as a Javanese customary inheritance mechanism that determines the two-to-one inheritance rate for sons and daughters. This study aims to assess the existence of the concept of sepikul segendongan in the present era and its relevance to the development of modern Javanese society. This research is an empirical study with a socio-legal approach, through inductive field studies with participatory observation and in-depth interviews to obtain primary data, while secondary data is obtained through literature studies. Data analysis coincided with data collection to find the formulation of specific questions in the interview. The results of this study indicate that the concept of inheritance of sepikul segendongan is a Javanese customary inheritance concept derived from Islamic law, as stipulated in QS. An-Nisa verse 11, but in the current era the community has actually begun to abandon the concept, because it is considered irrational for several reasons. First, the concept is considered not to reflect mathematical justice. Secondly, most respondents did not know that the concept was an implementation of Islamic law. Third, the concept is seen as an outdated custom, and is no longer relevant to the individual rights of each heir.